Expansion Of The Grubi Snacks Market Through Business Legality And Packaging Redesign - Fariskha, Titin (Prosiding University Research Colloquium, 2022)
Berkah Bumi Micro, Small and Medium Enterprises located in Truni Hamlet, Candisari Village, Windusari District, Magelang Regency are a productive business unit that empowers women by processing local commodities, namely Madusari sweet potato into processed snacks. One of the processed products is grubi or yam kremes, in the form of chopped sweet potato fried dry and mixed with melted brown sugar. By deploying 20 workers, especially housewives, the grubi products have been marketed outside the island. Generally, the grubi cake is taken by traders or sent to distributors to be repackaged, so that the packaging is perfunctory which is important to protect the entire product. In addition, the product has not been used for Home Industry Food, the production process, especially printing, is still carried out manually, has not kept business records, and potato skin waste has not been used or thrown away and the packaging is still not modern. In connection with this, assistance will be provided to Berkah Bumi Micro, Small and Medium Enterprises with through the Integrated Community Service (PPMT) at Muhammadiyah Magelang University which involves 5 students with the chief executive of a lecturer. Activities will be carried out for approximately 1 month or at least meet 150 hours. The method used to provide assistance is a participatory method that involves partners actively in all series of activities. The mentoring activities carried out included mentoring for Home Industry Food submissions, updating logo and packaging designs, processing sweet potato skin waste into organic fertilizer and training in simple software for bookkeeping and making grubi printing machines. The results of PPMT activities for approximately 1 month are Taxpayer Identification Numbers (NPWP) for partners as a requirement for making Home Industry Food, Online Single Submission accounts for submitting Business Identification Numbers, logo designs and new packaging designs, processing waste from sweet potato skins into fertilizer, simple software to help with bookkeeping, and the design concept of a grub printing machine.